PEMANFAATAN ELEMEN DAUR ULANG PADA DESAIN TAMAN LALU LINTAS TK BAITHANI TENGGER PADA KEGIATAN SERVICE LEARNING KELAS ARSITEKTUR ANAK DI NONGKOJAJAR – JAWA TIMUR - Christine Wonoseputro; Jessica Muljadi; Marcelina Lupita Surjanto; Keshia Hanna Kumala; Stevanie Paulina; Leonita Theodore; Fransiskus Xaverius Jonathan Tjiptorahardjo; Wilson Tedja (SHARE: Journal of Service Learning, 2015)
The Service Learning method that being done in TK Baithani Tengger, was not just a community service activity. In the process of learning, students were trained in order to be able to analyze community problems and continued to take it as design problem of their project. In the other side, students also learn to cooperate with all parties in the implementation of real project development, especially by utilizing ceramic scrap materials in order to be used as finishing elements of TK Baithani Tengger’s traffic education park.